STRUKTUR KOMUNITAS GASTROPODA DI DANAU SIPOGAS KABUPATEN ROKAN HULU PROVINSI RIAU - Erlinda, Lia; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about community and structure of Gastropods in Sipogas Lake Rokan Hulu Regency Riau Province has been conducted in August to December 2014 by using survey method and line transect techniques. Samples were collected by using by eckman dredge end hand collecting in line transect. Result showed 4 families, 6 species. Density values ranged from 0.1-9.4 individual /m2, diversity index value ranged from 0-1.21 can be concluded in low and moderate category, similarity index value ranged from 0-1 can be concluded in similar and non-similar deployment, dominance index value ranged 0.33-1.